EMPOWERMENT OF FISH CULTIVATION GROUPS (POKDAKAN) IN THE MINAPOLITAN AREA OF KALANGANYAR VILLAGE, SEDATI DISTRICT, SIDOARJO REGENCY - Mutia Ristina Nur Aini; Susi Hardjati (DIA: Jurnal Administrasi Publik, 2021)
Kalanganyar Village, Sedati District, Sidoarjo Regency is a village with the nickname "Kampung Iwak" with very abundant milkfish potential. This study aims to determine the stages of community empowerment that have been carried out and provide an in-depth description of the empowerment of Fish Cultivation Groups (POKDAKAN) in the Minapolitan Area, Kalanganyar Village, Sedati District, Sidoarjo Regency. This study uses a type of qualitative descriptive research in the form of words, and actions from the mouth of people and from observable behavior. Which leads to explain a thing or problem that occurs with a picture according to the focus of the research problem. Sources of data used come from primary and secondary data sources through data collection techniques with observation, interviews and documentation.Based on the findings in the field, this study shows that the stages of empowerment that have been carried out by POKDAKAN in Kalanganyar Village are starting from enabling, empowering, and protecting various programs that have been implemented, starting from awareness efforts, establishing institutional systems, training, providing capital, providing facilities and infrastructure, marketing of fishery products, and other protection measures which include the existence of a POKDAKAN Certificate which is already a legal entity from the Ministry of Law and Human Rights and the existence of a KUSUKA card as an insurance card, database center and to facilitate access to capital loans. Keywords: Community Empowerment, POKDAKAN